2020
DOI: 10.1002/saj2.20091
|View full text |Cite
|
Sign up to set email alerts
|

Relating four‐day soil respiration to corn nitrogen fertilizer needs across 49 U.S. Midwest fields

Abstract: Soil microbes drive biological functions that mediate chemical and physical processes necessary for plants to sustain growth. Laboratory soil respiration has been proposed as one universal soil health indicator representing these functions, potentially informing crop and soil management decisions. Research is needed to test the premise that soil respiration is helpful for profitable in‐season nitrogen (N) rate management decisions in corn (Zea mays L.). The objective of this research was two‐fold: (i) determin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 65 publications
0
13
1
Order By: Relevance
“…Our results of nonsignificant difference in 1dC and 4dC between N fertilization treatments in Sidney was also in contrast with that obtained by Sainju, Caesar-Tonthat, Lenssen, and Barsotti (2012) who reported greater flush with 80 than with 0 kg N ha −1 . Mac Bean et al (2020) found that N fertilization decreased 4dC compared with no N fertilization at four sites but did not affect it at 45 sites in U.S. Midwest. Nitrogen fertilization can variably affect CO 2 flux (Al-Kaisi et al, 2008;Sainju et al, 2010).…”
Section: Co 2 Flushesmentioning
confidence: 92%
See 4 more Smart Citations
“…Our results of nonsignificant difference in 1dC and 4dC between N fertilization treatments in Sidney was also in contrast with that obtained by Sainju, Caesar-Tonthat, Lenssen, and Barsotti (2012) who reported greater flush with 80 than with 0 kg N ha −1 . Mac Bean et al (2020) found that N fertilization decreased 4dC compared with no N fertilization at four sites but did not affect it at 45 sites in U.S. Midwest. Nitrogen fertilization can variably affect CO 2 flux (Al-Kaisi et al, 2008;Sainju et al, 2010).…”
Section: Co 2 Flushesmentioning
confidence: 92%
“…Several researchers (Haney et al, 2001;Franzluebbers, 2016) also reported that CO 2 flushes at 1-to 3-d incubations were related to forage N uptake. Others (Mac Bean et al, 2020;Roper et al, 2017) found that 4dC was not consistently related to crop yield, although significant relationship occurred in years with favorable weather condition. They suggested that the relationship should be examined in regions with particular soil type, climatic condition, and management practice rather than using it for the comprehensive interpretation of soil health indicator for broad regions.…”
Section: Relationship Between Co 2 Flush and Crop Yieldmentioning
confidence: 96%
See 3 more Smart Citations